DIVERSIFIKASI PRODUK OLAHAN KREATIF HASIL PERTANIAN BERBASIS IPTEK: KUNCI PEMBERDAYAAN EKONOMI KWT TIRTA RAHAYU - Beta Asteria; Sulastiningsih; Muhammad Subkhan; Dimas Rizky Kurniawan; Rafif Raditya Muhrizal (Jurnal Edukasi Pengabdian Masyarakat, 2026)
The Tirta Rahayu Women's Farmers Group, located in Tamanan Village, Banguntapan Subdistrict, Bantul Regency, is highly motivated to support local food security. However, the group faces several challenges, including a lack of understanding of creative processed products, attractive packaging, and limited digital marketing. Therefore, this community service program aims to increase production capacity through creativity in product diversification. The methods used in this community service program include outreach, production management training, and packaging training to increase the value of agricultural products. The results of this program indicate that diversified products for sale from fruit and vegetables are produced, such as vegetable nuggets, healthy juice, vegetable chips, and vegetable package. These products have economic value and represent an innovation to optimize fruit and vegetable consumption among children who do not like them. This demonstrates that production assistance can strengthen farming capacity, increase product sales value, and have an economic impact on women's farming groups in a creative and independent manner.